2016
DOI: 10.1080/19345747.2016.1204640
|View full text |Cite
|
Sign up to set email alerts
|

Does Early Mathematics Intervention Change the Processes Underlying Children's Learning?

Abstract: Early educational intervention effects typically fade in the years following treatment, and few studies have investigated why achievement impacts diminish over time. The current study tested the effects of a preschool mathematics intervention on two aspects of children’s mathematical development. We tested for separate effects of the intervention on “state” (occasion-specific) and “trait” (relatively stable) variability in mathematics achievement. Results indicated that, although the treatment had a large impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Indeed, using the National Longitudinal Survey of Youth, Lin et al (2018) recently found that associations between general cognitive ability (IQ) and earnings increased over the span of participants' careers. However, these findings may not translate to more narrowly defined achievement skills, as other work has shown that intervention-spurred changes in mathematics skills may not lead to changes in general cognitive ability (Bailey et al, 2014;Watts et al, 2017). Thus, we still lack estimates of the long-run returns to more narrowly defined achievement skills, which are often the focus of educational programs.…”
mentioning
confidence: 90%
“…Indeed, using the National Longitudinal Survey of Youth, Lin et al (2018) recently found that associations between general cognitive ability (IQ) and earnings increased over the span of participants' careers. However, these findings may not translate to more narrowly defined achievement skills, as other work has shown that intervention-spurred changes in mathematics skills may not lead to changes in general cognitive ability (Bailey et al, 2014;Watts et al, 2017). Thus, we still lack estimates of the long-run returns to more narrowly defined achievement skills, which are often the focus of educational programs.…”
mentioning
confidence: 90%
“…Fourth, the model can be easily adapted into an experimental design, in which the first wave of post-treatment achievement and the stable latent variable are simultaneously regressed on treatment status. Relying on the TRIAD data used above, Watts and colleagues (2016) found a substantial impact of the intervention on children’s math skills, but no effect on the latent variable representing stable factors that influence children’s achievement across development. However, this finding warrants replication under conditions in which persistence may be most likely, including for subgroups, treatments, and populations for which skills affected by the intervention are least likely to develop under counterfactual conditions.…”
Section: An Alternative Developmental Modelmentioning
confidence: 98%
“…The REMA assessed children’s conceptual and procedural knowledge, as well as problem-solving and strategic competencies in the domain of early mathematics, and has been shown to strongly correlate with other measures of early math learning (e.g., Applied Problems, Child Math Assessment ). Further it has been shown to strongly predict later mathematics achievement measured through grade 5 (Watts, Duncan, Clements, & Sarama, 2016). Thus, the REMA should provide a strong measure of the early mathematical competencies needed to build later skills in mathematics.…”
Section: Riskier Testsmentioning
confidence: 99%
“…In this respect, our results of the lowest skill profile are similar to Datar (2006) who shows that younger entrance age for kindergarten negatively affects the economically and cognitively lowest group of the sample. Recognition of the negative association of schooling and specific mathematical skills in a particular sub-group of children adds educationally-relevant knowledge to previous variable-centered research findings, which showed positive educational effects on early numeracy on average level (Bojorque et al, 2016;Hannula, Mattinen & Lehtinen, 2005;Watts et al, 2017). Identifying these kinds of unique associations on sub-populations can be educationally beneficial when dealing with heterogeneous populations (Abenavoli, Greenberg, & Bierman, 2017).…”
Section: Discussionmentioning
confidence: 63%